Characterization of Maleimide-Based Glycogen Synthase Kinase-3 (GSK-3) Inhibitors as Stimulators of Steroidogenesis - Gunosewoyo, Hendra; Midzak, A.; Gaisina, I.; Sabath, E.; Fedolak, A.; Hanania, T.; Brunner, D.; Papadopoulos, V.; Kozikowski, A. (American Chemical Society, 2013)
Inhibition of GSK-3β has been well documented to account for the behavioral actions of the mood stabilizer lithium in various animal models of mood disorders. Recent studies have showed that genetic or pharmacological inhibition of GSK-3β resulted in anxiolytic-like and pro-social behavior. In our ongoing efforts to develop GSK-3β inhibitors for the treatment of mood disorders, SAR studies on maleimide-based compounds were undertaken. We present herein for the first time that some of these GSK-3β inhibitors, in particular analogues 1 and 9, were able to stimulate progesterone production in the MA-10 mouse tumor Leydig cell model of steroidogenesis without any significant toxicity. These two compounds were tested in the SmartCube behavioral assay and showed anxiolytic-like signatures following daily dose administration (50 mg/kg, ip) for 13 days. Taken together, these results support the hypothesis that GSK-3β inhibition could influence neuroactive steroid production thereby mediating the modulation of anxiety-like behavior in vivo.